2021
DOI: 10.1108/ijshe-07-2020-0275
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable strategic planning in Italian higher education institutions: a content analysis

Abstract: Purpose This study aims, first of all, to analyze the extent to which Italian higher education institutions declare their mission statements in their official documents; then, to examine their content; and finally, to investigate whether mission statements include considerations on sustainability dimensions. Design/methodology/approach After a theoretical background on the new strategic approach adopted by higher education institutions and the related disclosure of their mission statements, the study deepens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…Finally, our study findings indicated that GLREA universities which posted, mentioned, and defined specifically their VMS count 37% of all 30 selected universities in the study. These findings are consistently found in Italian HEIs (Fantauzzi et al, 2021 ).…”
Section: Discussion Of Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Finally, our study findings indicated that GLREA universities which posted, mentioned, and defined specifically their VMS count 37% of all 30 selected universities in the study. These findings are consistently found in Italian HEIs (Fantauzzi et al, 2021 ).…”
Section: Discussion Of Resultssupporting
confidence: 70%
“…These authors argued that the twin terms are vital strategic tools which direct institutional planning, establish work scope, determine strategic operations and purpose, create values, establish and define institutional commitments and outcomes, and help institutions focus on what truly matters to all of its stakeholders. In other contexts (i.e., the US, the UK, and Europe as a whole), scholars analyzed data collected from different websites and found that the twin terms do not only provide necessary information about a university, but also attract its key stakeholders (Ahmad & Masroor, 2020 ; Fantauzzi et al, 2021 ). Lee and Park ( 2021 ) emphasized that VMS present universities’ images and portray them as public good producers and globally competitive strategic actors.…”
Section: Literatue Review Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, from this framework, and responding to the call from academics for more studies on SR in universities, this paper contributes to the previous literature with a study on the principal management tool through which universities nowadays establish and manage to set their strategic objectives regarding the issues of SR: the strategic plan. Following prior studies (Fantauzzi et al 2021;Sangiorgi and Siboni 2017) we adopted a qualitative approach applying the content analysis technique (Low et al 2015) to a selected sample of strategic plans issued by Italian universities. Based on these observations, this study addressed the following research question: RQ.…”
Section: Introductionmentioning
confidence: 99%
“…In a context where the concept of sustainability has become so important, representing one of the columns of social and economic development and a new challenge to excellence for any school that is widely accepted to play a teaching role, teachers and administrators have been called to extend their activities, presenting themselves as operators for social change [32].…”
Section: Sustainability Remarksmentioning
confidence: 99%